Real-world tafamidis experience in hereditary transthyretin amyloidosis with peripheral neuropathy in Brazil - Pinto, Luiz Felipe; Pinto, Marcus V.; Accioli, Paula; Amorim, Gabriela; Rosa, Renata Gervais de Santa; Dias, Moises; Guedes, Mariana; Gomez, Carlos P.; Pedrosa, Roberto C.; Waddington-Cruz, Marcia (Arquivos de Neuro-Psiquiatria, 2025)
Background Tafamidis is a kinetic stabilizer that binds to the transthyretin (TTR) gene, inhibiting its dissociation. It is the only disease-modifying treatment for hereditary TTR amyloidosis with peripheral neuropathy (ATTRv-PN) available in the National Therapeutic Form (Formulário Terapêutico Nacional, FTN, in Portuguese) of the Brazilian Unified Health System (Sistema Único de Saúde, SUS, in Portuguese).Objective To assess if the efficacy and safety of tafamidis in the Brazilian real-world experience are comparable to the results of clinical trials.Methods We retrospectively studied all patients with ATTRv-PN evaluated at our center from September 2011 to March 2022 (data cut-off) who were initiated on tafamidis and had at least 1 follow up visit 6 months after the initiation of the drug treatment. Neurologic and functional outcomes were compared from day 1 (D1) of the tafamidis treatment (baseline) to the last follow-up.Results In total, 33 patients were included, 18 (55%) of whom were female. All patients were carriers of the V30M mutation of ATTRv-PN, and 20 (61%) presented early onset (EO) ATTRv-PN. At baseline, the median age of the sample was of 40 (interquartile range [IQR]: 36–68) years, the median Neuropathy Impairment Score (NIS) was of 10 (6–24) points, and the median body mass index (BMI) was of 26 (23–28) kg/m2. The mean follow-up time was of 3.4 years. At the last follow-up, the BMI, the neurological impairment, and the level of disability slightly worsened compared with baseline, while the findings of the nerve conduction studies remained stable. These same results were observed across EO and late-onset (LO) ATTRv-PN patients. A total of 25 (75.8%) patients were considered responders, and 8 (24.2%), non-responders.Conclusion The efficacy and safety of tafamidis reported in clinical trials is expandable to the Brazilian real-world scenario in EO and late-onset (LO) ATTRv-PN.
Keywords: Polyneuropathies; Prealbumin; Amyloid Neuropathies, Familial; Amyloidosis, Familial